Pengaruh Rasio Profitabilitas, Likuiditas, Dan Solvabilitas Terhadap Peringkat Obligasi Syariah (Sukuk) - Frivanty Ekatiarta Nuriman; Dian Hakip Nurdiyansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of ratio profitability, liquidity and leverage on sharia bond rating (sukuk). The research method in this study uses a quantitative apporoach. There were 13 companies that were used as populations in this study and by using a purposive sampling technique 4 sampels were also obtained. The statistical methods taken in the study are multiple regression analysis using classic assumption test. Based on the variable T test of profitability, it obtained tcount 2.974 > ttable 2.030 and significant value of 0.004 < 0.05. It means that return on asset positively and partially affected sukuk rating. Liquidity obtained tcount -8.927 < ttable 2.030 and significant value of 0.000 < 0.05. It means that Current Ratio partially affected sukuk rating. Leverage ratio obtained tcount 3.362 > ttable 2.030 and significant value of 0.001 < 0.05. It means that Debt to Equity Ratio partially affected sukuk rating. Furthermore, analysis of F test obtained fcount 26.800 > ftable 2.76 and significant value obtained was 0.000 < 0.05 which means that independent variable simultaneously affected sukuk rating. Keywords: Profitability, Liquidity, Leverage and Rating Sukuk